PERAN DKPP DALAM MENEGAKKAN KODE ETIK PENYELENGGARA PEMILU DAN MEWUJUDKAN PILKADA BERMARTABAT - Feka, Mikhael; Witarti Rabawati, Dwityas; Arman, Yohanes; Taemenas, Egidius (JAP UNWIRA, 2020)
AbstractThe Honorary Council for General Election Organizers  (DKPP) is an element in the general election execution together with the General Election Commission (KPU) and the General Election Supervision Body (Bawaslu). The main function of the DKPP is to enforce the ethical code for the general election organizers. A dignified general election and election of district heads starts from the general election organizers who are supposed to uphold the general election ethics, although that does not constitute a single factor, in a sense that a dignified general election should be the responsibility of all elements of general election that include the organizers, the pair candidates, political parties, success team, civil servants, national and districts governments, as well as other stakeholders. The problem is that the DKPP’s authority  is limited to the execution of the general election and does not cover the whole system of the carrying out of the general election and therefore it is difficult to realize a dignified election of district heads, despite the fact that a dignified election will bring about dignified leaders. As a democratic country, Indonesia is supposed to consider not only ethical code for the general election organizers but also ethical code for the whole implementation of the general election.
Keywords: DKPP, ethics, dignified general election